2005
DOI: 10.1142/s1088424605000344
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new carboran-based phthalocyanines and study of their activities in the photooxidation of citronellol

Abstract: The synthesis and characterization of novel phthalocyanines containing o-carborane groups are described. These new tetrasubstituted phthalocyanines are of interest for the use in cancer therapy. The activities of the carboranyl substituted phthalocyanines were evaluated by the photooxidation of (S)-(-)-citronellol to give a high oxygen consumption comparable to the photosensitizers tetrasulfophthalocyanine zinc complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 15 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…An alternative route based on acylation of zinc phthalocyanines bearing aniline and phenol terminal groups with the corresponding ortho-carboranyl acylchlorides gave 5 and 6 in 65 and 53 % yields, respectively (Scheme 4). [35] In a similar way the reaction of zinc acetate with 3-[4-(ortho-carboran-1-yl) methylphenoxy]phthalonitrile at 210 ºC gave the boronated zinc phthalocyanine 7 in 40 % yield (Scheme 4). [36,37] It was demonstrated that boronated phthalocyanine 7 can be efficiently accumulated by B16F1 melanotic melanoma cells in vitro and, upon red light irradiation, induced extensive cell mortality.…”
Section: Polyhedral Boron Compoundsmentioning
confidence: 94%
“…An alternative route based on acylation of zinc phthalocyanines bearing aniline and phenol terminal groups with the corresponding ortho-carboranyl acylchlorides gave 5 and 6 in 65 and 53 % yields, respectively (Scheme 4). [35] In a similar way the reaction of zinc acetate with 3-[4-(ortho-carboran-1-yl) methylphenoxy]phthalonitrile at 210 ºC gave the boronated zinc phthalocyanine 7 in 40 % yield (Scheme 4). [36,37] It was demonstrated that boronated phthalocyanine 7 can be efficiently accumulated by B16F1 melanotic melanoma cells in vitro and, upon red light irradiation, induced extensive cell mortality.…”
Section: Polyhedral Boron Compoundsmentioning
confidence: 94%
“…Owing to their structural analogy with porphyrins, some phthalocyanines have been investigated as potential boron carriers [124], as is exemplified by the boronated metal-phthalocyanine 73 prepared by Kahl et al. [125] ( Figure 5).…”
Section: Figurementioning
confidence: 99%
“…After the first paper reviewed this field, [109] only a few reports have been published [124][125][126][127][128] (Scheme 10).…”
Section: Scheme 8 Boron-containing Porphyrinsmentioning
confidence: 99%
“…[ -, prepared previously for a BNCT project, [13a] was used for radiolabeling of proteins. This compound was labeled with 125 I and coupled to anti-HER2/neu humanized antibody trastuzumab [149] (Scheme 13). The study of the biodistribution of a radioconjugate prepared in mice revealed decreased radioactivity uptake by the thyroid in comparison with the directly radiolabeled antibody.…”
Section: Polyhedral Boron Hydrides As Carriers Of Radiohalogen Labelsmentioning
confidence: 99%